1988
DOI: 10.1128/aac.32.4.458
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo activities of sedecamycin against Treponema hyodysenteriae

Abstract: Sedecamycin (lankacidin A), one of the lankacidin-group antibiotics, showed potent activity against Treponema hyodysenteriae. The MICs of sedecamycin against 79 field isolates of T. hyodysenteriae ranged from 0.78 to 12.5 ,Ig/ml, the MIC for 90% of the strains tested (MIC90) being 3.13 ,ug/ml. The protective and therapeutic effects of sedecamycin were compared with those of carbadox, tiamulin, and lincomycin against experimental infection with T. hyodysenteriae in mice. The protective effect of sedecamycin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…318–323 The acyclic substrate LC-KA05 ( 456 ) is formed by a hybrid NRPS-PKS assembly line with γ-lactone formation as the termination and product release step. 324 Concerted desaturation of the secondary amine to the product iminium ( 457 ) and capture by the enol carbon to create the new C-N bond that forms the 17 atom macrocycle lankacidinol A ( 458 ) is catalyzed by the enzyme LkcE (Scheme 64).…”
Section: Nonradical Cyclization Mechanismsmentioning
confidence: 99%
“…318–323 The acyclic substrate LC-KA05 ( 456 ) is formed by a hybrid NRPS-PKS assembly line with γ-lactone formation as the termination and product release step. 324 Concerted desaturation of the secondary amine to the product iminium ( 457 ) and capture by the enol carbon to create the new C-N bond that forms the 17 atom macrocycle lankacidinol A ( 458 ) is catalyzed by the enzyme LkcE (Scheme 64).…”
Section: Nonradical Cyclization Mechanismsmentioning
confidence: 99%
“…T. hyodysenteriae DJ70P3 (11), which is pathogenic in mice, was used. The inoculum was prepared as described previously (23 the probit method (17) from the rate at which T. hyodysenteriae was eradicated from the cecum.…”
Section: Methodsmentioning
confidence: 99%
“…By using this animal model, we have shown that orally administered sedecamycin, a 17-member macrocyclic antibiotic (Fig. 1), shows good efficacy in mice (11).…”
mentioning
confidence: 99%
“…Sedecamycin was developed in the authors' research laboratories and exhibited remarkable effects o n swine dysentery caused by Serpulina hyodysenteriae, not only in experimental swine infection models, but also in natural outbreaks in the field trials (YAMAZAKI et al, 1986;HAYASHI et al, 1988;TSUBOTA, 1989). Terdecamycin {(-)-N-[( lS, 2R, 7S, 13S, 15R, 19R)-(3E, 5E, 9E, 11E)-13-hydroxy-7-(4-methylpiperazino)carbonyloxy-1,4,10,19-tetramethyl-17,18-dioxo-16-oxabicyclo[l3.2.…”
Section: Introductionmentioning
confidence: 99%